2019
DOI: 10.4142/jvs.2019.20.e6
|View full text |Cite
|
Sign up to set email alerts
|

Carriage ofStaphylococcus schleiferifrom canine otitis externa: antimicrobial resistance profiles and virulence factors associated with skin infection

Abstract: The recent emergence of Staphylococcus schleiferi in dogs with otitis externa or skin and soft tissue infections has become a significant zoonotic issues. In the current study, we investigated 1) the carriage rates of S. schleiferi among major staphylococci in healthy dogs and dogs with otitis externa, 2) antibiotic susceptibility profiles of S. schleiferi, particularly methicillin resistance (MR), and 3) virulence factors associated with ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
5
32
0
Order By: Relevance
“…With regards to skin and ear infections and consistent with other studies, Staphylococcus coagulase-positive (CoPS), and in particular Staphylococcus pseudointermedius, was the most common organism isolated [8][9][10][11]. This was followed by Staphylococcus coagulase-negatives (CoNS), which other studies have identified mostly as S. schleiferi.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With regards to skin and ear infections and consistent with other studies, Staphylococcus coagulase-positive (CoPS), and in particular Staphylococcus pseudointermedius, was the most common organism isolated [8][9][10][11]. This was followed by Staphylococcus coagulase-negatives (CoNS), which other studies have identified mostly as S. schleiferi.…”
Section: Discussionsupporting
confidence: 84%
“…They also showed that multi-drug resistant isolates occurred almost exclusively in CoNS for cats, but it was almost equally distributed between the CoNS and CoPS groups for dogs. Thus, the clinical significance of CoNS may not only be as opportunistic pathogens [ 8 ], but also as clear potential reservoirs of antimicrobial resistance genes that can be transferred to CoPS. Except for the skin, we found a much higher prevalence (6–10 fold) of CoPS than CoNS in samples from ears, wounds, nasal cavity, and abscesses; whether this implies a clinically relevant association is unknown, as the pathogenicity of CoNS has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the frequency of hemolytic agent genes of hla, hlb, hld were higher in cefoxitin resistant isolates compared to susceptible ones. [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The coagulase-positive Staphylococcus pseudointermedius is the most detected species in both healthy and sick dogs, and it is assumed that it is host-adapted [ 9 ]. Though with a lower detection rate, other CoPS and CoNS can be isolated and cause diseases in dogs: Staphylococcus aureus , Staphylococcus schleiferi , Staphylococcus epidermidis , Staphylococcus haemolyticus , Staphylococcus saprophyticus , Staphylococcus sciuri , and Staphylococcus warneri [ 10 , 11 , 12 ]. The exact arrangement of different Staphylococcus species as saprophytic, commensal, opportunistic, or pathogens for dogs is still under evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been focused on the discovery of some bacterial or host factors that could be at the basis of disease development, even if a mix of these factors are probably involved [ 1 , 7 , 9 , 13 ]. Regarding the bacterial side, different virulence factors have been detected in strains isolated from dogs, in particular from skin lesions, including different types of exfoliative toxins, leucocidins, superantigens, enterotoxins, invasion enzymes, and biofilm producers [ 10 , 11 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%